MATHEMATICAL MODEL OF THE HUMAN VISUAL ORGAN BASED ON THE COMPARISON METHOD - Токарєв, Володимир (SWorldJournal, 2025)
Abstract. In the work, the comparison method widely used in colorimetric experiments is used to model the functions of human vision. To solve this class of problems, a mathematical model was obtained with the help of predicates of a special type. It is p